Anti-inflammatory activity of berries driven polyphenols in zebrafish larvae fed with oxidizedlipids and LPS - Bento, Luís Filipe Martins (2022)
Inflammation is aconserved process throughout nature, as it is a fundamental part in the immune response of an organism when dealing with a strange molecule, being endogenous or exogenous. This system relies on the coordination of different immune cells for an effective response. The tissue resident cells (macrophages and dendritic cells) when activated start to produce and secret cytokines and chemokines to signal other immune cells (monocytes and neutrophils) to move and differentiate to the injury site. This process creates a great amount of stress on the tissues and cells around it and if left unresolved it starts to damage healthy tissues. Therefore, it is crucial that we can fully understand this process to find treatments capable of aiding the endogenous immune system. Zebrafish has been used in the study of chronic diseases for some time, as it possesses big advantages for the study of cell behavior and immunity, like transparency on the larval stage, a similar innate immune system to humans and an easily alterable genome. This makes it a perfect model for the study of the inflammatory response. The main objective of this work was to evaluate the response of macrophages during an inflammatory response and test polyphenolic compounds for their anti-inflammatory characteristics as potential tools for treatment of inflammation in chronic diseases. E. coliLPS and a high fat diet, with increased content of cholesteryl hemiazelate (ChA) were used as the inflammatory stimuli. Presenting these inflammatory molecules to the 6 day-post fertilization larvae resulted in an increase in the number of macrophages recruited to the caudal vein, an injury-prone region. Pre-incubating the polyphenolic compounds showed a reduction on macrophage numbers close to control levels in some cases. Altogether, this work allowed for the confirmation that polyphenolic compounds have an anti-inflammatory effect opening possibilities for new treatments.